2014
DOI: 10.1177/0961203314522334
|View full text |Cite
|
Sign up to set email alerts
|

Association of extended interleukin-10 promoter haplotypes with disease susceptibility and manifestations in German patients with systemic lupus erythematosus

Abstract: Our data confirm that the complexity of the IL-10 promoter evokes the need for a meticulous analysis of its haplotypic structure in order to specify disease associations, particularly under functional aspects, thereby shedding light on the pathophysiology of SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
(86 reference statements)
1
7
1
Order By: Relevance
“…As in previous studies, complexity of the IL-10 promoter with respect to functional aspects is reflected by the fact that the observed associations are generally stronger when the analysis is extended to haplotypes [ 31 ]. Thus, substantial information is gained when the structure of genetic elements is resolved to haplotypes rather than being restricted to the single nucleotide polymorphisms.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As in previous studies, complexity of the IL-10 promoter with respect to functional aspects is reflected by the fact that the observed associations are generally stronger when the analysis is extended to haplotypes [ 31 ]. Thus, substantial information is gained when the structure of genetic elements is resolved to haplotypes rather than being restricted to the single nucleotide polymorphisms.…”
Section: Discussionmentioning
confidence: 83%
“…BigDye 3.1 standard DNA-sequencing reactions were performed in a Gene Amp PCR System 9700, followed by capillary electrophoresis done on an ABI 3730XL sequencer (Applied Biosystems, Weiterstadt, Germany). Raw data analyses and the call of SNPs were done with the SeqScape v2.7 software (Applied Biosystems, Weiterstadt Germany) [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…(2014) reported that the GGCC haplotype was protective against SLE in a German population. 16 They constructed haplotypes using one SNP (IL-10-2849A/G) from the distal region of IL-10 promoter. However, haplotypes containing proximal promoter polymorphisms (−1082, −819, −592) did not show a significant difference between patient and control groups in a German population.…”
Section: Resultsmentioning
confidence: 99%
“…15 SNPs in both distal (3575 T/A, −2849 G/A, −2763 C/A) and proximal regions (−1082 A/G, −819 T/C, −592 C/A) have been reported to influence disease susceptibility among different populations. 6,16 Nevertheless, polymorphisms (−1082A/G, −819T/C, −592C/A) from proximal regions are abundantly studied. However, the results describing genotypic and haplotype analysis are inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that the IL-10 -1082G/A gene polymorphism is associated with several types of chronic inflammatory diseases, including systemic lupus erythematosus, rheumatoid arthritis, deep venous thrombosis, and sepsis (Zhang et al, 2011;Ouyang et al, 2013;Schotte et al, 2014;Tang et al, 2014). Zhang et al (2011) reported that the A allele of IL-10 -1082A/G polymorphism was associated with an increased risk of rheumatoid arthritis in a Chinese population.…”
Section: Discussionmentioning
confidence: 97%